Choice of secondary prevention improves risk factors after acute coronary syndrome: 1-year follow-up of the CHOICE (Choice of Health Options In prevention of Cardiovascular Events) randomised controlled trial. Issue 6 (18th September 2008) - Redfern, J; Briffa, T; Ellis, E; Freedman, S B
Abstract : Objective: To determine the effect of a new CHOICE (Choice of Health Options In prevention of Cardiovascular Events) programme on cardiovascular risk factors in acute coronary syndrome (ACS) survivors. Design: Single-blind randomised controlled trial. Setting: Tertiary referral hospital in Sydney Australia. Patients: 144 ACS survivors who were not accessing standard cardiac rehabilitation. Data were also collected on a further 64 ACS survivors attending standard cardiac rehabilitation. Intervention: The CHOICE group (n = 72) participated in a brief, patient-centred, modular programme comprising a clinic visit plus telephone support, encompassing mandatory cholesterol lowering and tailored preferential risk modification. The control group (n = 72) participated in continuing conventional care but no centrally coordinated secondary prevention. Main outcome measures: Values for total cholesterol, systolic blood pressure, smoking status and physical activity. Results: CHOICE and control groups were well matched at baseline. At 12 months, the CHOICE group (n = 67) had significantly better risk factor levels than controls (n = 69) for total cholesterol (TC) (mean (SEM) 4.0 (0.1) vs 4.7 (0.1) mmol/l, p<0.001), systolic blood pressure (131.6 (1.8) vs 143.9 (2.3) mm Hg, p<0.001), body mass index (28.9 (0.7) vs 31.2 (0.7) kg/m 2, p = 0.025) and physical activity (1369.1 (167.2) vs 715.1 (103.5) METS/kg/min, p = 0.001) as well as a better knowledge of risk factor targets. Also at 1 year, fewer CHOICE participants (21%) had three or more risk factors above widely recommended levels then controls (72%) (p<0.001). Conclusions: Participation in a brief CHOICE programme significantly improved the modifiable risk profiles and risk factor knowledge of ACS survivors over 12 months. CHOICE is an effective alternative for dealing with the widespread underuse of existing secondary prevention programmes. Trial registration number: ISRCTN42984084